Clinicopathological characteristics and outcomes of ROS1‐rearranged patients with lung adenocarcinoma without EGFR, KRAS mutations and ALK rearrangements. Issue 4 (July 2015) - Wu, Shafei; Wang, Jinghui; Zhou, Lijuan; Su, Dan; Liu, Yuanyuan; Liang, Xiaolong; Zhang, Shucai; Zeng, Xuan
Abstract Background c‐ros oncogene 1 (ROS1) rearrangement presents one of the newest molecular targets in non‐small cell lung cancer (NSCLC). ROS1 rearrangement is predominantly found in adenocarcinoma cases and is exclusive to other oncogenes, such as epidermal growth factor receptor (EGFR), Kirsten rat sarcoma viral oncogene homolog (KRAS), and anaplastic lymphoma kinase (ALK). The aim of this study was to investigate the clinicopathological characteristics and outcomes of ROS1‐rearranged patients with lung adenocarcinoma without EGFR and KRAS mutations and ALK rearrangements. Methods Wild‐type EGFR/KRAS/ALK patients with lung adenocarcinoma were selected from Beijing Chest Hospital. Specimens were conducted in tissue microarrays. ROS1 rearrangement was screened using fluorescence in situ hybridization. Results Our study included 127 patients with lung adenocarcinoma without EGFR and KRAS mutations and ALK rearrangements. ROS1 rearrangement was detected in five (3.9%) of the 127 patients. Compared with ROS1‐negative patients, the positive rate of ROS1 in female patients was significantly higher than in male patients (9.8% vs. 0.0%, P = 0.009). There were no differences in age, smoking status, stage or histological subtype between ROS1‐positive and ROS1‐negative patients. No significant difference in survival was detected between the ROS1‐positive and ROS1‐negative patients. Conclusions ROS1 rearrangement is a rare subset of lung adenocarcinoma. In 127 patients with lung adenocarcinoma, 3.9% of ROS1‐positive patients with wild‐type EGFR/KRAS/ALK were found.